2013
DOI: 10.1097/fjc.0b013e318287d526
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Milk–derived Lactoferrin Exerts Proangiogenic Effects in an Src-Akt-eNOS–dependent Manner in Response to Ischemia

Abstract: Lactoferrin (LF) exerts a variety of biological effects, including the promotion of angiogenesis by increasing the expression of angiogenesis-related genes and reducing blood pressure via a nitric oxide-dependent mechanism. In this study, we investigated the effects of LF on angiogenesis using C57BL/6J mice that received daily unilateral treatment with or without bovine milk-derived LF (bLF) after unilateral hindlimb surgery. The analysis of laser speckle blood flow showed that bLF treatment promoted blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…It has been suggested that the vasodilatory action of LF is strongly mediated by NO production because of complete blockade of this effect by a NO synthase inhibitor [19]. Ikeda and coworkers have reported significant phosphorylation of Src, Akt, and endothelial nitric oxide synthase (eNOS) after treatment with LF suggesting a Src Akt eNOS-dependent pathway in promotion of vascular endothelial cell function by LF [31]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the vasodilatory action of LF is strongly mediated by NO production because of complete blockade of this effect by a NO synthase inhibitor [19]. Ikeda and coworkers have reported significant phosphorylation of Src, Akt, and endothelial nitric oxide synthase (eNOS) after treatment with LF suggesting a Src Akt eNOS-dependent pathway in promotion of vascular endothelial cell function by LF [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding could improve endothelial function, primarily due to the presence of lactoferrin, an iron-binding glycoprotein with antioxidant, anti-inflammatory, pro-angiogenic and NO-dependent vasodilator properties. Daily treatment with lactoferrin after unilateral hind limb surgery-induced ischemia in C57BL/6J mice promoted angiogenesis, activated endothelial function via an NO-dependent mechanism 171 and protected HUVECs against hydrogen peroxide-induced oxidative stress 172 …”
Section: Potential Preventive Approachesmentioning
confidence: 99%
“…20 Capillary density and arterioles number Capillary density was estimated by CD31 immunohistochemistry. 20,21 Briefly, 28 days after surgery, adductor muscles were snap frozen in liquid nitrogencold isopentane containing optimal cutting temperature compound and cut into 8 μm cryosections. Capillary density was expressed as the number of CD31-positive cells corrected for the number of muscle fibers.…”
Section: Evaluation Of Peripheral Blood Flowmentioning
confidence: 99%
“…20,21 Briefly, 1 × 10 4 HAECs were cultured per well of Matrigel-coated 96-well plate in the presence of each concentration of bilirubin or vehicle, with or without 2 μM LY294002. Cells were then incubated at 37°C for 18 h. The formation of tube-like structures were observed using an inverted contrast microscope and captured with a CCD camera.…”
Section: Tube-like Formation Assaymentioning
confidence: 99%